A sustainable solution for diclofenac adsorption: Chitosan-modified fibrous silica KCC-1 adsorbent - Lai, L. W.; Teh, L. P.; Timmiati, S. N.; N. H. N., Kamarudin; Herma Dina, Setiabudi (Elsevier Ltd, 2023)
This work aims to assess the potential of chitosan/fibrous silica KCC-1 composite in diclofenac adsorption. Fibrous silica KCC-1 was synthesized by microemulsion technique and chitosan/fibrous silica KCC-1 composite was prepared by ultrasound assisted impregnation. The physical and chemical properties were characterized by using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), point zero charge (PZC) and N2 physisorption. The removal of diclofenac was analysed through ultraviolet-visible spectroscopy (UV-Vis) under different parameters such as contact time, pH value and initial concentration of diclofenac. The characterization results showed that chitosan/fibrous silica KCC-1 composite has an amorphous structure with dendritic morphology, good thermal stability, various functional groups such as amine and hydroxyl that act as the active site for diclofenac adsorption, large surface area of 510 m2/g and total pore size of 0.4922 cm3/g, as well as pHPZC at pH 4.6 for efficient removal of diclofenac. The results showed that chitosan/fibrous silica KCC-1 composite can interact and adsorb more diclofenac as compared to pure fibrous silica KCC-1. Chitosan/fibrous silica KCC-1 composite gives an adsorption capacity of 142.01 mg/g whereas fibrous silica KCC-1 gives an adsorption capacity of 65.33 mg/g under the optimum contact time at 40 min, pH value of 4.0 and initial concentration of diclofenac at 160 mg/L. Langmuir adsorption isotherm and Elovich kinetic model resulted to be the best fit for diclofenac adsorption by chitosan/fibrous silica KCC-1 composite with the R2 value of 0.9721 and 0.9597, respectively.